Full recovery of right ventricular systolic function in children undergoing bilateral lung transplantation for severe PAH - Hansmann, Georg; Diekmann, Franziska; Chouvarine, Philippe; Ius, Fabio; Carlens, Julia; Schwerk, Nicolaus; Warnecke, Gregor; Vogel-Claussen, Jens; Hohmann, Dagmar; Alten, Tim; Jack, Thomas (The journal of heart and lung transplantation, 2022)
Background - We investigated whether RV function recovers in children with pulmonary arterial hypertension (PAH) and RV failure undergoing lung transplantation (LuTx). - Methods - Prospective observational study of 15 consecutive children, 1.9 to 17.6 years old, with PAH undergoing bilateral LuTx. We performed advanced echocardiography (Echo) and cardiac magnetic resonance imaging (MRI), followed by conventional and strain analysis, pre- and ∼6 weeks post-LuTx. - Results - After LuTx, RV/LV end-systolic diameter ratio (Echo), RV volumes and systolic RV function (RVEF 63 vs 30 %; p < 0.05) by MRI completely normalized, even in children with severe RV failure (RVEF < 40%). The echocardiographic end-systolic LV eccentricity index nearly normalized post-LuTx (1.0 vs 2.0, p < 0.0001) while RV hypertrophy regressed more slowly and was still evident. We found especially the end-systolic RV/LV ratios by Echo (diameter: 0.6 vs 2.6) or MRI (volumes: 0.8 vs 3.4) excellent diagnostic tools (p < 0.05): Together with RVEF by MRI, these ratios were superior to tricuspid annular plane systolic excursion (TAPSE; p=0.4551) in assessing global systolic RV dysfunction. Moreover, children with severe PAH had reduced RV 2D longitudinal strain (Echo, MRI; p=0.0450) and decreased RV 2D radial and circumferential strain (MRI; p=0.0026 and p=0.0036 respectively), all of which greatly improved following LuTx. - Conclusion - We demonstrate full recovery of RV systolic function in children within two months after LuTx for severe PAH, independently of the patients’ age, weight, and hemodynamic compromise preceding the LuTx. Even in end-stage pediatric PAH with poor RV function and low cardiac output, LuTx should be preferred over heart-lung transplantation.
Available online 29 October 2021
Gesehen am 12.09.2022